REGIONALIZATION AND GLOBALIZATION: INTERNATIONAL PERSPECTIVE - Reutov , Viktor; Burkaltseva , Diana; Boychenko, Oleg; Velgosh, Nataliia; Shcheglova, Svetlana; Shkolnikova , Liliya (Revista Inclusiones, 2020)
The article analyzes the most important and general features of the processes of globalization as a major phenomenon in the modern world. This phenomenon takes place almost in any area of economic, political, social and cultural life, being one of the most important factors in international relations. Secondly, this paper aims at explaining the role of the European Union in regionalization processes, since the EU is one of the leading actors upon the global scene. This research requires to point out principal international conditions that influence processes of globalization, then to synthetically define what globalization is and finally, to explore the degree and the way in which the European Union has been involved therein.